Polyesteramide of neem oil and its blends as an active nanomaterial for tissue regeneration - Killi, Naresh; Pawar, Anil Tukaram; Gundloori, Rathna V. N. (ACS Applied Bio Materials, 2019)
Neem oil gained importance due to its antibacterial properties. Therefore, it is extensively being used for various applications. Oils can be polymerized as a polyesteramide to extend their utility as biomaterials. In our studies, we synthesized polyesteramide from neem oil and various compositions of blends were prepared with the drug, chlorohexidine digluconate (CH) to develop a nanomaterial for tissue regeneration. The studies such as cytotoxicity, biodegradable, antibacterial, in vitro drug release, in vivo wound healing, and histopathological studies were performed to identify their potential for tissue regeneration. In vivo wound healing studies of the nanofiber mats with and without CH recorded a faster healing rate as compared to the commercial cream (povidone–iodine). Most importantly, there was no requirement of repeated application of nanofiber mats during the treatment. The histopathology studies also suggested the re-epithelialization of the wounds. Hence, these nanomaterials are considered to be environmentally safe scaffolds for efficient tissue regeneration applications.